Invasive Pneumococcal Disease in Canadian Children, 2000-2014: The Canadian Immunization Monitoring Program, Active. (1st June 2016) - Bettinger, J; Scheifele, D; Kellner, J; Saux, N Le; Embree, J; Vanderkooi, O; Martin, I; Tyrrell, G; Vaudry, W; Halperin, S
Abstract: BACKGROUND: Before implementation of the first conjugate IPD vaccine program in 2002, invasive pneumococcal disease (IPD) accounted for most severe, invasive bacterial infections in Canadian children. Conjugate vaccine programs in children were implemented with the expectation that the burden of disease from IPD would improve. OBJECTIVES: To describe the changes in Canadian epidemiology of pediatric IPD before and after the implementation of conjugate pneumo-coccal vaccine programs. DESIGN/METHODS: The Canadian Immunization Monitoring Program, Active (IMPACT) captures all in- and out-patient lab-confirmed IPD cases presenting at its 12 tertiary care pediatric hospitals across Canada. Nurses abstract case details from the hospital chart onto a standardized report form. Case isolates are serotyped at a central reference laboratory. All participating centers have local ethics and/or administrative approvals. RESULTS: From 2000-2014 IMPACT centers identified 3, 328 IPD cases. Annual case numbers decreased by 48% (323 to 168) over this time period. Annually, vaccine preventable serotypes accounted for on average 89% (n=288) of cases in the pre-conjugate vaccine era (2000-2003) and 34% (n=56) in the post-13-valent conjugate vaccine era (2011-2014), with 73% (n=41/56) due to serotypes 19A, 3 and 6a. The age distribution of cases shifted upward over the time period with 16% (n=204) of cases occurring in children 5 years of age and older in the pre-vaccine era compared to 32% (n=217) in the post 13-valent vaccine era. This shift was due to decreases in cases occurring in children 0-4 years of age, rather than a significant increase in the number of cases occurring in older children. The most frequent presentation of IPD was radiologic-confirmed pneumonia (n=1119), with complicated pneumonia (pneumonia with empyema or pleural effusion) accounting for 36% (405/1119) of cases, followed by bacteremia only (n=919) and meningitis (n=532). The proportion of cases presenting with complicated pneumonia increased significantly (from 6% -24%; p<0.0001) between the pre-conjugate and post 13-valent conjugate eras. The proportion of cases presenting with meningitis did not change over the time periods (15% pre-conjugate era vs. 16% post-13-valent conjugate era; p=0.46). However, the proportion of meningitis caused by vaccine preventable serotypes decreased significantly (from 85%-26%; p<0.0001). CONCLUSION: The epidemiology of pediatric IPD has changed with the introduction of conjugate vaccine programs. IPD has been reduced by almost 50% in the post-13-valent conjugate vaccine era and vaccine sero-types account for just one-third of cases. However, complicated pneumonia is seen more frequently in the post-13-valent conjugate vaccine era.